Comparative inactivation of viruses by chlorine. - Engelbrecht, R S (1980)
The kinetics of inactivation of six enteric viruses plus simian virus 40 and Kilham rat virus by free available chlorine was studied under carefully controlled laboratory conditions. It was found that the different virus types demonstrated a wide range of susceptibility to chlorine disinfection. The rate of inactivation was greater at pH 6 than at pH 10; however, the relative susceptibilities of the different viruses were affected differently by a change in pH, suggesting that the pH influenced both the species of chlorine present and the susceptibility of the different viruses to chlorine. The presence of potassium chloride also affected the susceptibility of viruses to chlorine.